JUSTIFICATION OF THE NEED TO ASSESS THE CAPABILITIES OF THE MILITARY UNITS OF THE NATIONAL GUARD OF UKRAINE FOR PROTECTION AND DEFENSE OF OBJECTS OF CRITICAL INFRASTRUCTURE - Sukonko, Serhii; Rosliakov, Oleksiy (Honor and Law, 2023)
At the beginning of the full-scale invasion of the Russian Federation into the territory of Ukraine, the aggressor seized critical infrastructure facilities that were located in the occupied territories. Among especially dangerous objects of critical infrastructure there are two nuclear power plants: Chernobyl and Zaporozhye. So, the Chernobyl nuclear power plant was captured by Russian troops on February 24, 2022 and controlled by them until March 31, 2022. And the Zaporozhye NPP was captured by the invaders on March 4, 2022 and is under their control. Based on the analysis of certain events, it can be concluded that the units of the National Guard of Ukraine were unable to ensure the defense of the stations, which, in accordance with the current legislation, is their direct function. The reason for this was the mistakes made by the military authorities in assessing the capabilities of the military units of the National Guard of Ukraine for the protection of nuclear power plants for the defense of the facilities entrusted to them. The solution to this problem in the future may be to improve the theory of assessing the capabilities of the military units of the National Guard of Ukraine regarding the protection and defense of critical infrastructure. For this purpose, the article analyzes the existing scientific and methodological apparatus and policy documents on the organization and implementation of the protection and defense of critical infrastructure facilities under martial law by the military units of the National Guard of Ukraine. As a result of the analysis, some problems were identified in the defense of nuclear power plants, as well as in the organization of management at the tactical level during the organization of the defense of critical infrastructure facilities, including nuclear power plants. Also, directions for further research were identified, namely: the settlement of the issue of subordination in the performance of combat missions for the protection and defense of critical infrastructure facilities at the tactical level, as well as the improvement of the theory of assessing the capabilities of the military units of the National Guard of Ukraine for the protection and defense of nuclear power plants, taking into account modern threats.